Impact analysis of the traffic convoy system and toll pricing policy of the Suez Canal on the operations of a liner containership over a long-haul voyage. (17th April 2019) - Du, Yuquan; Meng, Qiang; Shi, Wenming
This paper takes an initiative to quantitatively assess the impact of the traffic control scheme and the stepwise toll pricing policy of the Suez Canal on the optimal sailing schedule of a liner containership. We develop a mixed-integer nonlinear programming model for the optimal sailing schedule of a containership over a long-haul voyage via Suez. A case study on a 13000-TEU containership running on the LP4 service of APL shows several managerial insights: a) ignoring the traffic control system at Suez in ship speed optimisation may lead to an infeasible sailing schedule, and underestimate the operating cost (even the bunker cost) of a containership on a long-haul voyage via Suez; b) the optimal ship recovery plan in terms of its sailing speeds is mainly determined by the predefined port time windows, delay situation and Suez-clock time, but not pretty much affected by the levels of bunker price and transit due.